2008
DOI: 10.1521/jscp.2008.27.8.809
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Guilt, Shame, Behavioral and Characterological Self-Blame to Depressive Symptoms in Adolescents Over Time

Abstract: In a two-wave, longitudinal study, 221 nonreferred adolescents completed measures of guilt, shame, Behavioral self-blame (BSB), Characterological self-blame (CSB), depressive symptoms measures, and attributional style. Goals were to examine similarities between Tangney's (1996) conceptualization of guilt and shame and Janoff-Bulman's (1979) conceptualization of BSB and CSB in adolescents. Specific aims were (1) to examine the relation of depressive symptoms and depressive cognitions to shame, guilt, CSB, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 81 publications
9
53
0
2
Order By: Relevance
“…Guilt involves moral transgressions (real or imagined) in which people believe that their action (or inaction) contributed to negative outcomes. Studies have found links between guilt and morality and behavioral-self blame (Lutwak, Panish, & Ferrari, 2003; Ruma & Mosher, 1967; Tilghman-Osborne, Cole, Felton, & Ciesla, 2008). A sense of responsibility and painful feelings of remorse are part of the guilt experience; however, whether or not atonement or reparations follow guilt is a separate question.…”
Section: Discussionmentioning
confidence: 99%
“…Guilt involves moral transgressions (real or imagined) in which people believe that their action (or inaction) contributed to negative outcomes. Studies have found links between guilt and morality and behavioral-self blame (Lutwak, Panish, & Ferrari, 2003; Ruma & Mosher, 1967; Tilghman-Osborne, Cole, Felton, & Ciesla, 2008). A sense of responsibility and painful feelings of remorse are part of the guilt experience; however, whether or not atonement or reparations follow guilt is a separate question.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural self-blame was defined as involving internal and unstable attributions of negative events to one’s own controllable behaviour [12] and was associated with feelings of guilt [12,14,15,16], whereas characterological self-blame was defined as blaming oneself for things that one has no control over, such as relatively enduring character traits [12]. The latter thereby entails a global (overgeneral) form of self-blame and such maladaptive devaluation of the ‘whole’ self was hypothesized to be associated with feelings of shame [13,14,15,16,17]. In contrast, work by O’Connor and colleagues provides evidence against the general association of guilt-proneness with behavioural self-blame by identifying characterological forms of empathy-based guilt [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, shame- rather than guilt-proneness has been associated with severity of depressive symptoms in healthy populations with no history of MDD [17,23]. In people with MDD, however, elevations in both shame- and guilt-proneness have been reported using different questionnaires [21,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding psychological adjustment, when one uses measures that are sensitive to the distinction between focusing on the self vs. the behavior [see 20], research on adults consistently shows a positive relationship between proneness to shame and a variety of psychological symptoms, including depression, anxiety, somatic symptoms, obsessive-compulsive tendencies, and paranoid ideation [2126, see 27 for a meta-analytic review of shame and depression, 28, 29]. Although fewer studies in this domain focus on children and adolescents, results are similar to those found in adult samples, demonstrating a link between shame-proneness and psychological symptoms among youth [3032, see 33 for a review, 34]. In contrast, proneness to “shame-free” guilt is generally negligibly or negatively related to psychological symptoms among children, adolescents, and adults [23, 2830, 35–38].…”
mentioning
confidence: 99%